Healing in the New Testament Insights from medical and Mediterranean Anthropology - Pilch, John J. (Minneapolis Fortress Press, 2000)
"How are we to read and understand stories about Jesus healing the lame, deaf, blind, and those with a variety of other maladies? Pilch takes us beyond the historical and literary questions to examine the social questions of how the ancient Judeans and
Keywords: Bible. -- Gospels -- Criticism, interpretation, etc. Healing in the Bible. Medical anthropology